Comparison of pre and post Global longitudinal Strain imaging in thrombolytic and primary percutaneous coronary intervention in acute ST elevation Anterior Myocardial infarction - Mandal, Mohammad Rayhan Masum; Ahsan, Syed Ali; Hoque, Harisul; Kabir, Mohammad Faisal Ibn; ahmed, Khurshed; Khaled, Fakrul Islam; Mahbub, Smear E; Fatema, Nilufar (University Heart Journal, 2020)
Abstract not available University Heart Journal Vol. 16, No. 1, Jan 2020; 11-15